2020
DOI: 10.1530/ec-20-0274
|View full text |Cite
|
Sign up to set email alerts
|

Why do so many trials of vitamin D supplementation fail?

Abstract: Abstract. Our knowledge of vitamin D has come a long way since the 100 years it took for doctors to accept, between 1860-1890, that both sunlight and cod liver oil [a well-known folk remedy] cured and prevented rickets.1]Vitamins D2/3 were discovered exactly a hundred years ago and over the last 50 years vitamin D has been found to have many effects on virtually all human tissues and not just on bone health, while mechanisms effecting the actions of vitamin D at the cellular level are increasingly understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 105 publications
(111 reference statements)
2
40
0
Order By: Relevance
“…Numerous observational epidemiological studies in humans have shown significant associations of low 25(OH)D concentrations with increased (current and future) health risks, in line with the various known actions of vitamin D. However, RCTs, the ‘gold standard’ for assessing the efficacy of treatments, and meta-analyses, have frequently failed to provide supportive evidence for the expected health benefits of vitamin D supplementation [ 73 , 74 ]. Such RCTs have used designs developed for testing drugs while vitamin D is a nutrient, in which a different rational should guide trial designs.…”
Section: Vitamin D Actionsmentioning
confidence: 99%
“…Numerous observational epidemiological studies in humans have shown significant associations of low 25(OH)D concentrations with increased (current and future) health risks, in line with the various known actions of vitamin D. However, RCTs, the ‘gold standard’ for assessing the efficacy of treatments, and meta-analyses, have frequently failed to provide supportive evidence for the expected health benefits of vitamin D supplementation [ 73 , 74 ]. Such RCTs have used designs developed for testing drugs while vitamin D is a nutrient, in which a different rational should guide trial designs.…”
Section: Vitamin D Actionsmentioning
confidence: 99%
“…Some, but not all, studies found positive effects for supplementation in respiratory infections including influenza ( 66 , 68 ). Interpretation in such studies, is complicated by disagreement concerning serum levels of calcidiol required for sufficiency ( 198 ), multiple confounding factors ( 18 , 120 , 121 ) and the application of methods designed for testing drugs rather than nutrients ( 140 , 141 ).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…More recently, Boucher further explores Heaney’s ideas and additional factors complicating analysis of vitamin D supplementation studies ( 141 ); further confounding issues are also discussed elsewhere ( 18 , 120 , 121 ).…”
Section: Cancermentioning
confidence: 99%
“…There are of course other reasons for some of the negative trial results, including vitamin D being treated as a drug rather than a nutrient, often with inclusion of many participants with normal vitamin D status at baseline. 35…”
Section: A Plausible Biological Mechanism Underlies the Lack Of Efficmentioning
confidence: 99%